Protection of the cultural elements and traditional expressions of indigenous and local communities: The prohibition to register a trademark of subparagraph g) of article 136 of the Decision 486 - Arana Courrejolles, María del Carmen (2017)
The present paper seeks to introduce a reflection about the protection of the cultural elements and traditional expressions of the indigenous and local communities, locating the pertinent law, the Andean Prejudicial Interpretation and its application on different cases.For that purpose, this investigation will focus on some cases from Peru and Colombia, under the ruling of Decision 486, identifying the way and content used by the competent administrative authority to decide on some trademark application, considering the prohibition contained in the paragraph g) of article 136 of the referred Decision.